PEMBIASAAN MEMBACA ASMAUL HUSNA SEBELUM MASUK KELAS DALAM MEMBENTUK KARAKTER RELIGIUS - Miftahudin, Miftahudin; Muslimin, Muslimin; Muchozin, Muhammad Ni'an; Zurtiana, Ahmad; Isya, Mandanu Akhta Nur; Aziz, Alvi; Yusrian, Afif Ramdhan (AL-QALAM: JURNAL ILMU KEPENDIDIKAN, 2024)
Moral, ethical or moral education at madrasah ibtidaiyah is the first basic or initial part of character formation for students. What is happening now is that character education is troubling parents. Education in class 1A of Madrasah Ibdtidaiyah Negeri 3 Banjarnegara has implemented character education as a response to the current damage to character education. Formation of morals, manners, morals or character through the habit of reading Asmaul Husna which is able to change students' religious character. This research aims to determine the application of reading Asmaul Husna which consists of the habit of reading Asmaul Husna in forming a religious character. This research was conducted in Class 1A MI N 3 Banjarnegara. This research uses a qualitative approach. Data collection techniques, namely documentation, observation and interviews. Then the data is analyzed by condensing the data, presenting the data and drawing conclusions. Research results: the habit of reading Asmaul Husna in forming the religious character of students at MI N 3 Banjarnegara is good. This is evidenced by the increasing religiousness in reading asmaul husna with reverence in reading asmaul husna, and with the intention of only hoping for the pleasure of Allah SWT. The reading of asmaul husna is done before learning begins. MI N 3 Banjarnegara holds prayers through reading asmaul husna in the hope that it will be easier to gain knowledge. beneficial in this world and the hereafter, making the mind calmer.